Apoptotic neutrophils augment the inflammatory response to Mycobacterium tuberculosis infection in human macrophages. - Henrik Andersson; Blanka Andersson; Daniel Eklund; Eyler Ngoh; Alexander Persson; Kristoffer Svensson; Maria Lerm; Robert Blomgran; Olle Stendahl (PLoS ONE)
Macrophages in the lung are the primary cells being infected by Mycobacterium tuberculosis (Mtb) during the initial manifestation of tuberculosis. Since the adaptive immune response to Mtb is delayed, innate immune cells such as macrophages and neutrophils mount the early immune protection against this intracellular pathogen. Neutrophils are short-lived cells and removal of apoptotic cells by resident macrophages is a key event in the resolution of inflammation and tissue repair. Since anti-inflammatory activity is not compatible with effective immunity to intracellular pathogens, we therefore investigated how uptake of apoptotic neutrophils modulates the function of Mtb-activated human macrophages. We show that Mtb infection exerts a potent proinflammatory activation of human macrophages with enhanced gene activation and release of proinflammatory cytokines and that this response was augmented by apoptotic neutrophils. The enhanced macrophage response is linked to apoptotic neutrophil-driven activation of the NLRP3 inflammasome and subsequent IL-1β signalling. We also demonstrate that apoptotic neutrophils not only modulate the inflammatory response, but also enhance the capacity of infected macrophages to control intracellular growth of virulent Mtb. Taken together, these results suggest a novel role for apoptotic neutrophils in the modulation of the macrophage-dependent inflammatory response contributing to the early control of Mtb infection.